Renormalization group analysis for thermal turbulence - D. N. Riahi (International Journal of Mathematics and Mathematical Sciences)
Renormalization group theory is applied to thermal turbulence. Turbulent fluxes for the flow are accounted for by repeatedly recasting the governing equations with the smallest scales represented by effective larger scales. Expressions for nonlinear contributions to eddy viscosity and eddy diffusivity are determined, and leading order contributions due to buoyancy on various results and equations are estimated. Proper scalings for various quantities and variables including temperature are proposed. The results near two fixed points, which correspond to inertial and buoyancy dominated ranges, are determined and discussed